Evaluation of the macroseismic intensities triggered by the January/February 2014 Cephalonia, (Greece) earthquakes based on ESI-07 scale and their comparison to 1867 historical event. (7th September 2017) - Papathanassiou, George; Valkaniotis, Sotirios; Ganas, Athanassios
Abstract: On January 26th and February 3rd, 2014, two earthquakes occurred onshore the island of Cephalonia inducing severe environmental effects. The main types of earthquake-induced failures were liquefaction and slope failures and were mainly widespread at the western and central part of the island at Paliki peninsula. Although the fact that the generated strong motions by the second event were the highest ever recorded in Greece, medium severity structural damages were induced. Few days after the occurrence of the events, two post-earthquake field surveys took place in order to document the generated environmental effects. By taking into account these field observations, it was decided to evaluate the macroseismic intensity of the February 3rd, 2014 earthquake by applying the ESI-07 scale. As an outcome, the epicentral intensity of Feb. 3rd, 2014 was evaluated as VII ESI-07 by taking into account the total affected area. Furthermore, as it is pointed out in primary contemporary sources and seismic catalogues, similar environmental failures such as liquefaction phenomena at coastal areas and large scale rockfalls were triggered by historical earthquakes at the island of Cephalonia. The most accurately described effects are the ones triggered by the 1867 earthquake. Therefore, it was decided to assess the macroseismic intensities of this historical event based on the ESI-07 scale and compare it with the relevant ones of Feb 3rd, 2014 event. As an outcome, it is concluded that similar intensities were assessed for both events, VIII ESI-07 for 1867 event and VII ESI-07 for the February 2014 one, despite the fact that the relevant earthquake magnitudes strongly differ. Outlining the results of this study, it is reconfirmed the importance of the recording and documentation of earthquake environmental effects in order to maintain the consistency with the historical earthquake catalogues. Moreover, a re-evaluation of historical earthquake magnitudes at the area of Cephalonia island could be realized in order to accurately update the seismic hazard.